EFFECTIVENESS OF IMPLEMENTING THE RPTRA PROGRAM IN CREATING A CHILD FRIENDLY CITY IN SUNGAI BAMBU DISTRICT, NORTH JAKARTA ADMINISTRATIVE CITY - Rokaiyah, Rokaiyah; Noer, Khaerul Umam; Satispi, Evi; Salam, Rahmat (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Children often do not get their rights even to grow and develop in accordance with their dignity and dignity as human beings. The number of violence against children in DKI Jakarta continues to increase every year.The government has also rolled out a policy (KLA) as a solution in providing child protection based on the decision of the Minister of State for Women's Empowerment and Child Protection of the Republic of Indonesia Number 56 of 2010 concerning the designation and determination of 20 provinces to develop child-friendly districts/cities, one of which is the DKI Jakarta province which is the pilot KLA development project. One of the policies owned by DKI Jakarta that supports KLA is the construction and deployment of RPTRAs.According to the KLA program there are 5 KLA clusters, namely firstCivil Rights and Freedoms, second, family environment and alternative care, third, basic health and welfare, fourth, education, use of free time & cultural activities, these five special protections are basic guidelines for activities at the Sungai Bambu RPTRA. The aim of this research is to see how far the program has run and to find out the results of program evaluation using the CIPP evaluation model. This research uses a qualitative descriptive approach, namely research carried out to obtain a clear picture of a particular incident. Data collection techniques were carried out using observation, interviews and documentation methods. The results of this research show that the implementation of the Sungai Bambu RPTRA program is running effectively seen from the evaluation of context, input, process,